2016
DOI: 10.1080/14670100.2015.1114220
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception scores in cochlear implant recipients: An analysis of ceiling effects in the CUNY sentence test (Quiet) in post-lingually deafened cochlear implant recipients

Abstract: Objectives: To evaluate the clinical utility of the CUNY sentence test in a cohort of post-lingually deafened CI recipients over time. The distribution of all post-operative CUNY test scores skewed to the right with 82% of test scores reaching above 90%.Discussion: This study demonstrates that the CUNY test cannot be used as a valid tool to measure the speech perception skills of post-lingually deafened CI recipients over time. This may be overcome by using adaptive test protocols or linguistically, cognitivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
(51 reference statements)
0
11
0
1
Order By: Relevance
“…According to Boothroyd and Nittrouer (1988), sentences with high predictability result in higher scores than sentences with low predictability and are therefore more prone to ceiling effects. Ebrahimi-Madiseh, Eikelboom, Jayakody, and Atlas (2016) showed that a ceiling effect also exists in the City University of New York sentence test (Boothroyd, Hanin, & Hnath, 1985) if used in CI recipients. Gifford et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Boothroyd and Nittrouer (1988), sentences with high predictability result in higher scores than sentences with low predictability and are therefore more prone to ceiling effects. Ebrahimi-Madiseh, Eikelboom, Jayakody, and Atlas (2016) showed that a ceiling effect also exists in the City University of New York sentence test (Boothroyd, Hanin, & Hnath, 1985) if used in CI recipients. Gifford et al.…”
Section: Introductionmentioning
confidence: 99%
“…According to Boothroyd and Nittrouer (1988), sentences with high predictability result in higher scores than sentences with low predictability and are therefore more prone to ceiling effects. Ebrahimi-Madiseh, Eikelboom, Jayakody, and Atlas (2016) showed that a ceiling effect also exists in the City University of New York sentence test (Boothroyd, Hanin, & Hnath, 1985) if used in CI recipients. Gifford et al (2008) recommended the use of the Arizona Biomedical Institute sentence test (Spahr et al, 2012), because this test contains more difficult, less predictable sentences, spoken by different talkers in a casual style.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, clinicians have often not extended testing beyond speech intelligibility in quiet conditions. However, increasingly higher levels of CI performance suggest that testing in quiet does not sufficiently cover the difficulty range to document performance in current CI populations ( Ebrahimi-Madiseh, Eikelboom, Jayakody, & Atlas, 2016 ; Gifford, Shallop, & Peterson, 2008 ). Beyond the fact that testing in noise better reflects real-life situations than testing in quiet, it has also been shown that speech intelligibility in noise is a better metric for evaluating the maximum potential of bimodal aiding ( Dorman et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…V některých studiích se však prokázaly jako nevyužitelné z hlediska měření řečové percepce u postlingválně ohluchlých uživatelů KI (např. Gifford et al, 2008;Ebrahimi-Madiseh et al, 2016), a to z důvodu neposkytnutí validních údajů a reálného obrazu zlepšování poslechových dovedností pacienta v čase.…”
Section: Testy řEčové Percepce V Zahraničíunclassified